Ethylene Oxide in Blood of Ethylene-Exposed B6C3F1 Mice, Fischer 344 Rats, and Humans - Filser, Johannes Georg (Oxford University Press, 2013)
The gaseous olefin ethylene (ET) is metabolized in mammals to the carcinogenic epoxide ethylene oxide (EO). Although ET is the largest volume organic chemical worldwide, the EO burden in ET-exposed humans is still uncertain, and only limited data are available on the EO burden in ET-exposed rodents. Therefore, EO was quantified in blood of mice, rats, or 4 volunteers that were exposed once to constant atmospheric ET concentrations of between 1 and 10 000 ppm (rodents) or 5 and 50 ppm (humans). Both the compounds were determined by gas chromatography. At ET concentrations of between 1 and 10 000 ppm, areas under the concentration-time curves of EO in blood (µmol × h/l) ranged from 0.039 to 3.62 in mice and from 0.086 to 11.6 in rats. At ET concentrations ≤ 30 ppm, EO concentrations in blood were 8.7-fold higher in rats and 3.9-fold higher in mice than that in the volunteer with the highest EO burdens. Based on measured EO concentrations, levels of EO adducts to hemoglobin and lymphocyte DNA were calculated for diverse ET concentrations and compared with published adduct levels. For given ET exposure concentrations, there were good agreements between calculated and measured levels of adducts to hemoglobin in rats and humans and to DNA in rats and mice. Reported hemoglobin adduct levels in mice were higher than calculated ones. Furthermore, information is given on species-specific background adduct levels. In summary, the study provides most relevant data for an improved assessment of the human health risk from exposure to ET.